The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1161/atvbaha.113.303003
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Bilirubin Is Associated With Silent Cerebral Infarction

Abstract: 946S ilent cerebral infarction (SCI) is a cerebral infarction that is evident on brain imaging but is not associated with a clinical symptom. In most cases, SCI is found as a lacunar infarction, that is, a small, deep cerebral infarct caused by occlusion of small penetrating cerebral arteries. Recent studies demonstrated that the presence of SCI predicts transient ischemia attack, clinically overt stroke, cardiovascular disease, and dementia. 1-3 See accompanying editorial on page 702A large body of evidence h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 48 publications
2
36
1
Order By: Relevance
“…Multivariate logistic regression analysis revealed that higher total bilirubin was associated with a lower risk of silent cerebral infarction. 15 However, the bilirubin level in our ICH patients was higher than in control patients, and the discrepancy between our studies with above statement could be due to the bias caused by a limited number of our patients.…”
Section: Discussioncontrasting
confidence: 83%
“…Multivariate logistic regression analysis revealed that higher total bilirubin was associated with a lower risk of silent cerebral infarction. 15 However, the bilirubin level in our ICH patients was higher than in control patients, and the discrepancy between our studies with above statement could be due to the bias caused by a limited number of our patients.…”
Section: Discussioncontrasting
confidence: 83%
“…19,20 Collectively, the evidence from this 18 and other studies [11][12][13][14][15][16][17] supports the possibility that the early measurement of TB levels might be useful to assess the risk of silent cerebral infarction(s) and major stroke and that mildly elevated TB levels might protect from stroke events and from neurological damage in stroke.…”
Section: Targher Risk Of Ischemic Stroke 703supporting
confidence: 64%
“…In this scenario, the study published by Li et al 18 in this issue of the journal adds to the body of evidence showing, for the first time, a graded, inverse relationship between serum levels of TB (conjugated and unconjugated bilirubin) and increased prevalence of silent cerebral infarctions in middle-aged Chinese individuals. Notably, this relationship remained significant after adjusting for established stroke risk factors and potential confounders.…”
Section: See Accompanying Article On Page 946mentioning
confidence: 86%
“…All measurements were conducted by a single examiner who was blinded to the clinical data. The reproducibility and validity of the baPWV measurement using this method has been previously demonstrated (Li, Cao, Zhang, Li, andWang, 2014, Li, Meng, Meng, Yu, andWang, 2011).…”
Section: Measurement Of Bapwvmentioning
confidence: 72%